Congruent Incircles

Geometry Level 4

As shown in the figure A B C \triangle ABC has side lengths 13 13 , 14 14 and 15 15 . A cevian A D AD is drawn such that two congruent incircles are inscribed. If the inradius is a + b c a + b\sqrt{c} , where a a , b b and c c are integers with c c being square-free, submit a + b + c a+b+c .


The answer is 7.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

4 solutions


In this solution we use the fact that, in the case where the two incircles are congruent, the following relation holds: A D = s ( s a ) ( 1 ) AD=\sqrt{s\cdot \left( s-a \right)} \ \ \ \ \ (1) where a = B C a=BC and s s is the semiperimeter of A B C \triangle ABC .

This is problem 2.2.5 in Fukagawa, Hidetoshi, and Dan Pedhoe. 1989, Japanese temple geometry problems, Winnipeg: Charles Babbage Research Centre. In this book no solution is given, but you can find one here (problem 8).


In our triangle we have s = 13 + 14 + 15 2 = 21 s=\dfrac{13+14+15}{2}=21 .

Using formula ( 1 ) (1) , we get A D = 21 7 = 7 3 AD=\sqrt{21\cdot 7}=7\sqrt{3} .

Let C D = x CD=x . Then, D B = 14 x DB=14-x and by Stewart's Theorem on A B C \triangle ABC for the cevian A D AD we have

C D A B 2 + D B A C 2 = B C ( A D 2 + C D D B ) x 15 2 + ( 14 x ) 13 2 = 14 [ ( 7 3 ) 2 + x ( 14 x ) ] CD\cdot A{{B}^{2}}+DB\cdot A{{C}^{2}}=BC\cdot \left( A{{D}^{2}}+CD\cdot DB \right)\Rightarrow x\cdot {{15}^{2}}+\left( 14-x \right)\cdot {{13}^{2}}=14\cdot \left[ {{\left( 7\sqrt{3} \right)}^{2}}+x\cdot \left( 14-x \right) \right] which solves to x = 5 + 3 or x = 5 3 x=5+\sqrt{3} \text{ or } x=5-\sqrt{3}

Case 1 : x = 5 + 3 x=5+\sqrt{3}

Denoting by s 1 {{s}_{1}} and s 2 {{s}_{2}} the semiperimeters of A C D \triangle ACD and A B D \triangle ABD respectively, we have s 1 = 13 + ( 5 + 3 ) + 7 3 2 = 4 3 + 9 {{s}_{1}}=\dfrac{13+\left( 5+\sqrt{3} \right)+7\sqrt{3}}{2}=4\sqrt{3}+9 and s 2 = 15 + [ 14 ( 5 + 3 ) ] + 7 3 2 = 3 3 + 12 {{s}_{2}}=\dfrac{15+\left[ 14-\left( 5+\sqrt{3} \right) \right]+7\sqrt{3}}{2}=3\sqrt{3}+12 By Heron’s folmula [ A C D ] = ( 4 3 + 9 ) ( 4 3 4 ) ( 3 3 + 4 ) ( 9 3 3 ) = 30 + 6 3 \left[ ACD \right]=\sqrt{\left( 4\sqrt{3}+9 \right)\left( 4\sqrt{3}-4 \right)\left( 3\sqrt{3}+4 \right)\left( 9-3\sqrt{3} \right)}=30+6\sqrt{3} and [ A B D ] = ( 3 3 + 12 ) ( 12 4 3 ) ( 4 3 + 3 ) ( 3 3 3 ) = 54 6 3 \left[ ABD \right]=\sqrt{\left( 3\sqrt{3}+12 \right)\left( 12-4\sqrt{3} \right)\left( 4\sqrt{3}+3 \right)\left( 3\sqrt{3}-3 \right)}=54-6\sqrt{3} For the radii r 1 {{r}_{1}} and r 2 {{r}_{2}} of A C D \triangle ACD and A B D \triangle ABD respectively, we have

r 1 = [ A C D ] s 1 = 30 + 6 3 9 + 4 3 = 6 2 3 {{r}_{1}}=\dfrac{\left[ ACD \right]}{{{s}_{1}}}=\dfrac{30+6\sqrt{3}}{9+4\sqrt{3}}=6-2\sqrt{3} and r 2 = [ A B D ] s 2 = 54 6 3 12 + 3 3 = 6 2 3 {{r}_{2}}=\dfrac{\left[ ABD \right]}{{{s}_{2}}}=\dfrac{54-6\sqrt{3}}{12+3\sqrt{3}}=6-2\sqrt{3} We notice that r 1 = r 2 {{r}_{1}}={{r}_{2}} .

Case 2 : x = 5 3 x=5-\sqrt{3}

Working the same way we find that r 1 r 2 {{r}_{1}}\ne {{r}_{2}} , hence this value is rejected.

To conclude, the common radius of the two circles is r = 6 2 3 r=6-2\sqrt{3} .
For the answer, a + b + c = 6 2 + 3 = 7 a+b+c=6-2+3=\boxed{7} .

Confession: I couldn't prove this problem. I was unaware of its Sangaku origin (I thought it was original :)) and I am so glad you pointed this out. Also the "30 Sanagaku problems" paper looks fascinating. Thank you, @Thanos Petropoulos for such an informative solution.

Fletcher Mattox - 8 months ago

Log in to reply

Thanks! I thought you had this Sangaku problem in mind when you came with "Congruent Incircles". And thanks for giving me the oportunity to mention this nice sangaku problem. PS. This time, your circles were not 'almost' congruent :)

Thanos Petropoulos - 8 months ago
Chris Lewis
Oct 12, 2020

I hadn't seen the formula in @Thanos Petropoulos ' solution before, but it simplifies things a lot.

If the common inradius is r r , then the area of Δ A B C \Delta ABC is 1 2 r ( 13 + 14 + 15 + 2 A D ) = r ( 21 + A D ) \frac12 r(13+14+15+2AD)=r(21+AD)

(using the fact that a triangle's area is its inradius times its semiperimeter in both A B D ABD and A C D ACD ). It's easy to verify (Heron's formula) that the area of A B C ABC is 84 84 ; so r ( 21 + A D ) = 84 r(21+AD)=84

From the formula Thanos quotes, A D = 21 7 = 147 AD=\sqrt{21\cdot 7}=\sqrt{147}

So r = 84 21 + 147 = 6 2 3 r=\frac{84}{21+\sqrt{147}}=6-2\sqrt3

giving the answer 7 \boxed7 .

Excellent simplification!

Thanos Petropoulos - 8 months ago
Mark Hennings
Oct 12, 2020

The triangle A B C ABC is a 5 , 12 , 13 5,12,13 triangle stuck to a 9 , 12 , 15 9,12,15 triangle, and hence has height 12 12 . Suppose that B D = x BD = x and A D = d AD = d . Then A C D ACD has area 6 ( 14 x ) 6(14-x) and semiperimeter 1 2 ( 27 x + d ) \tfrac12(27-x+d) , while A B D ABD has area 6 x 6x and semiperimeter 1 2 ( 15 + x + d ) \tfrac12(15+x+d) . Thus we deduce that 12 ( 14 x ) 27 x + d = 12 x 15 + x + d ( 14 x ) ( 15 + x + d ) = x ( 27 x + d ) 210 x + 14 d x 2 x d = 27 x x 2 + x d 210 28 x = 2 ( x 7 ) d 7 ( 15 2 x ) = ( x 7 ) d \begin{aligned} \frac{12(14-x)}{27 - x + d} & = \; \frac{12x}{15+x+d} \\ (14-x)(15 + x + d) & = \; x(27-x+d) \\ 210 - x + 14d - x^2 - xd & = \; 27x - x^2 + xd \\ 210 - 28x & = \; 2(x-7)d \\ 7(15 - 2x) & = \; (x-7)d \end{aligned} Thus we deduce that 7 < x < 7 1 2 7 < x < 7\tfrac12 and moreover, since cos B = 3 5 \cos B = \tfrac35 , we deduce that d 2 = 225 + x 2 18 x d^2 = 225 + x^2 - 18x , so that 49 ( 15 2 x ) 2 = ( x 7 ) 2 ( x 2 18 x + 225 ) 196 x 2 2940 x + 11025 = x 4 32 x 3 + 526 x 2 4032 x + 11025 x 4 32 x 3 + 330 x 2 1092 x = 0 x ( x 14 ) ( x 2 18 x + 78 ) = 0 x ( x 14 ) ( ( x 9 ) 2 3 ) = 0 \begin{aligned} 49(15 - 2x)^2 & = \; (x - 7)^2(x^2 - 18x + 225) \\ 196x^2 - 2940x + 11025 & = \; x^4 - 32x^3 + 526x^2 - 4032x + 11025 \\ x^4 - 32x^3 + 330x^2 - 1092x & = \; 0 \\ x(x - 14)(x^2 - 18x + 78) & = \; 0 \\ x(x -14)\big((x-9)^2 - 3\big) & = \; 0 \end{aligned} Since 7 < x < 7 1 2 7 < x < 7\tfrac12 , we deduce that x = 9 3 x = 9 - \sqrt{3} , so that d = 7 3 d = 7\sqrt{3} and hence the common inradius is 12 x 15 + x + d = 6 2 3 \frac{12x}{15+x+d} \; = \; 6 - 2\sqrt{3} making the answer 6 + ( 2 ) + 3 = 7 6 + (-2) + 3 = \boxed{7} .

Nice work, I tried a similar approach but missed the cosine rule connection. Thank you.

Fletcher Mattox - 8 months ago
Chew-Seong Cheong
Oct 13, 2020

By cosine rule , we have 1 5 2 = 1 3 2 + 1 4 2 2 ( 13 ) ( 14 ) cos C 15^2 = 13^2+14^2 - 2(13)(14)\cos C . cos C = 5 13 \implies \cos C = \dfrac 5{13} . Then altitude of A B C \triangle ABC is 13 sin C = 12 13 \sin C = 12 . Let the inradius be r r , C D = x CD=x , and A D = AD = \ell . Then the areas of A C D \triangle ACD and A D B \triangle ADB are given by:

{ [ A C D ] = 13 + x + 2 r = 12 x 2 ( 13 + x + ) r = 12 x . . . ( 1 ) [ A D B ] = 29 x + 2 r = 12 ( 14 x ) 2 ( 29 x + ) r = 12 ( 14 x ) . . . ( 2 ) \begin{cases} [ACD] = \dfrac {13+x+\ell}2r = \dfrac {12x}2 & \implies (13+x+\ell) r = 12 x &...(1) \\ [ADB] = \dfrac {29-x+\ell}2r = \dfrac {12(14-x)}2 & \implies (29-x+\ell) r = 12(14-x) &...(2) \end{cases}

From ( 1 ) ( 2 ) \dfrac {(1)}{(2)} :

13 + x + 29 x + = x 14 x 182 + x + 14 x 2 x = 29 x x 2 + x 91 14 x = ( x 7 ) Note that = ( x 5 ) 2 + 1 2 2 91 14 x = ( x 7 ) ( x 5 ) 2 + 1 2 2 x = 5 + 3 \begin{aligned} \frac {13+x+\ell}{29-x+\ell} & = \frac x{14-x} \\ 182 + x + 14 \ell - x^2 - x\ell & = 29x - x^2 + x\ell \\ 91 - 14x & = (x-7) \blue \ell & \small \blue{\text{Note that }\ell = \sqrt{(x-5)^2+12^2}} \\ 91 - 14x & = (x-7) \blue{\sqrt{(x-5)^2+12^2}} \\ \implies x & = 5+\sqrt 3 \end{aligned}

From ( 2 ) ( 1 ) (2)-(1) :

( 16 2 x ) r = 12 ( 14 2 x ) ( 8 x ) r = 12 ( 7 x ) r = 12 ( 7 x ) 8 x = 12 ( 7 5 3 ) 8 5 3 = 12 ( 2 3 ) 3 3 = 12 ( 2 3 ) ( 3 + 3 ) 6 = 2 ( 3 3 ) = 6 2 3 \begin{aligned} (16-2x)r & = 12(14-2x) \\ (8-x)r & = 12(7-x) \\ \implies r & = \frac {12(7-x)}{8-x} \\ & = \frac {12(7-5-\sqrt 3)}{8-5-\sqrt 3} \\ & = \frac {12(2-\sqrt 3)}{3-\sqrt 3} \\ & = \frac {12(2-\sqrt 3)(3+\sqrt 3)}6 \\ & = 2(3-\sqrt 3) = 6 - 2\sqrt 3 \end{aligned}

Therefore a + b + c = 6 2 + 3 = 7 a+b+c = 6-2+3 = \boxed 7 .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...